Temperature-specific adaptations and genetic requirements in a biofilm formed by Pseudomonas aeruginosa - Bisht, Karishma; Luecke, Alex R.; Wakeman, Catherine A. (Frontiers in Microbiology, 2023)
Pseudomonas aeruginosa is a gram-negative opportunistic pathogen often associated with nosocomial infections that are made more severe by this bacterium’s ability to form robust biofilms. A biofilm is a microbial community encompassing cells embedded within an extracellular polymeric substrate (EPS) matrix that is typically secreted by the encased microbial cells. Biofilm formation is influenced by several environmental cues, and temperature fluctuations are likely to be an important stimulus in the lifecycle of P. aeruginosa as it transitions between life in aquatic or soil environments to sites of infection in the human host. Previous work has demonstrated that human body temperature can induce a shift in the biofilm EPS relative to room temperature growth, resulting in an incorporation of a filamentous phage coat protein into the biofilm EPS. In this study, we sought to identify adaptations enabling biofilm formation at room temperature or temperatures mimicking the natural environment of P. aeruginosa (23 ˚C and 30 ˚C) relative to temperatures mimicking life in the human host (37 ˚C and 40 ˚C). We identified higher biofilm:biomass ratios at lower temperatures on certain substrates, which correlated with a higher relative abundance of apparent polysaccharide EPS content. However, the known genes for EPS polysaccharide production in P. aeruginosa PA14 did not appear to be specifically important for temperature-dependent biofilm adaptation, with the pelB gene appearing to be generally important and the algD gene being generally expendable in all conditions tested. Instead, we were able to identify two previously uncharacterized hypothetical proteins (PA14_50070 and PA14_67750) specifically required for biofilm formation at 23 ˚C and/or 30 ˚C relative to temperatures associated with the human host. These unstudied contributors to biofilm integrity may have been previously overlooked since most P. aeruginosa biofilm studies tend to use 37 ˚C growth temperatures. Overall, our study demonstrates that temperature shifts can have dramatic impacts on biofilm structure and highlights the importance of studying environment-specific adaptations in biofilm physiology.